Artificial intelligence anxiety in future healthcare professionals - Brown, Stephen (American Journal of Education and Learning, 2026)
The purpose of this article is to review current literature on health professionals’ anxiety related to the adoption of artificial intelligence technologies in the delivery of healthcare. The integration of Artificial Intelligence (AI) into the delivery of healthcare presents a transformative opportunity to both enhance patient care, and operational efficiencies. However, a potentially negative consequence of this integration has concurrently given rise to Artificial Intelligence Anxiety (AIA) among healthcare professionals, stemming from concerns about job security, ethical ambiguities, data privacy, and perceived lack of professional preparedness. Our findings suggest that an essential role of education is to address artificial intelligence anxiety in future healthcare professionals by providing appropriate education and training. These educational interventions should develop literacy in artificial intelligence technologies, and cultivate a collaborative, human-centred approach that frames AI as an augmentation tool, empowering healthcare professionals rather than replacing them. The practical implications of effective educational strategies should aim to build a resilient healthcare professional workforce where human expertise and AI capabilities synergistically optimize care delivery. We further suggest that providers of education, along with other stakeholders in the preparation and training of our future healthcare professional workforce, also need to contribute to the establishment of regulatory frameworks and policies which ensure ethical governance of AI.